Validation of noise induced hearing loss questionnaire among Malay sawmill workers in Kelantan Malaysia - Mohd Rus, Razman; Naing, Lin; Daud, Aziah; Musa, Kamarul Imran (Faculty of Medicine, International Islamic University Malaysia, 2010)
Introduction: Exposure to excessive noise is the major avoidable cause of permanent hearing impairment. Sawmill is one of the workplaces where workers are exposed to hazardous noise level. This study was conducted to determine the reliability and validity of noise-induced hearing loss questionnaire among sawmill workers. Materials and Methods: This cross sectional study was conducted in March 2007 among 35 consented sawmill workers. A total of 40 items; 10 items for knowledge (8 areas), 20 items for attitude (7 areas) and 10 items for practice (2 areas) were assessed. Statistical analysis for reliability analysis was test by internal consistency and construct validity by exploratory factor analysis using principal components and Varimax rotation method. Results: Cronbach’s alpha coeffi cients were acceptable for attitude (0.90) and practice (0.75). However, it was low for knowledge (0.67). Exploratory factor analysis showed three meaningful exploratory factors that could explain the three dimensions in the questionnaire. Conclusion: The results of the validation study suggested that the noise-induced hearing loss questionnaire is reliable and valid tool for assessing knowledge, attitude and practice among sawmill workers.